2019
DOI: 10.1111/jog.13893
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of intravenous ferric carboxymaltose and iron sucrose for the treatment of preoperative anemia in patients with menorrhagia: An open‐label, multicenter, randomized study

Abstract: Aim To compare ferric carboxymaltose (FCM) with iron sucrose (IS) for the effective and timely treatment of preoperative iron deficiency anemia (IDA) in women with menorrhagia. Methods This open‐label, multicenter, two‐arm study randomized patients to receive either a single dose of FCM or multiple doses of IS. The primary endpoint was the proportion of patients who achieved hemoglobin (Hb) levels ≥10 g/dL within 2 weeks after the first administration. Secondary endpoints included mean Hb levels, time to reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 25 publications
0
51
1
1
Order By: Relevance
“…We also identified a lack of guidance for the use of iron therapy, with only 8/22 guidelines providing some recommendations on this topic. This is somewhat surprising, given that iron therapy has been shown in multiple settings to be effective in women with HMB [70][71][72][73][74][75]. This may be because the guidelines are often targeted at specialists treating HMB, covering the diagnosis of ID/IDA as part of the HMB workup on the assumption that patients will then be referred to the family practitioner for treatment of any diagnosed ID/IDA.…”
Section: Discussionmentioning
confidence: 99%
“…We also identified a lack of guidance for the use of iron therapy, with only 8/22 guidelines providing some recommendations on this topic. This is somewhat surprising, given that iron therapy has been shown in multiple settings to be effective in women with HMB [70][71][72][73][74][75]. This may be because the guidelines are often targeted at specialists treating HMB, covering the diagnosis of ID/IDA as part of the HMB workup on the assumption that patients will then be referred to the family practitioner for treatment of any diagnosed ID/IDA.…”
Section: Discussionmentioning
confidence: 99%
“…Two randomized clinical studies have demonstrated that iron sucrose is effective for the correction of iron-deficiency anemia due to heavy menstrual bleeding (menorrhagia) [96,97]; in one study, 72% of women who received treatment with iron sucrose achieved Hb levels of at least 10 g/dL within 2 weeks after the first administration [96].…”
Section: General Women's Healthmentioning
confidence: 99%
“…No differences were found between clinical symptoms of anemia, psychological status, and AEs between groups Krafft and Breymann (2011) [ 91 ] Hb < 8.5 g/dL 24–48 h after delivery IS: 20 IS + ESA: 20 200 mg q.d., 4 days Hb values were close to normal in both groups within 2 weeks Both treatments were well tolerated; minor side effects included metallic taste in 30% of patients and warm flush in 8% of patients Wågström et al (2007) [ 92 ] Hb ≤ 80 g/dL within 72 h after delivery IS: 15 IS + rhEPO 1: 19 IS + rhEPO 2: 15 IS: 200 mg q.d., day 0, day 3 IS + rhEPO 1: IS 200 mg q.d., day 0, day 3 + rhEPO 10,000 U on day 0, day 3 IS + rhEPO 2: IS 200 mg q.d., day 0, day 3 + rhEPO 20,000 U on day 0, day 3 Hb increased significantly in all three groups over time ( p < 0.001), and there were no differences between the treatment groups on any day of evaluation ( p = 0.59). The total mean increment in Hb in all subjects was 18 g/dL after 1 week and 28 g/dL after 2 weeks Breymann et al (2000) [ 93 ] Hb < 10.0 g/dL IS: 20 IS + ESA: 20 Oral iron: 20 200 mg q.d., 4 days All three regimens were effective; day 7 hematocrit increases were higher with adjuvant ESA than for IS or oral iron alone: 8% versus 5% and 4%, respectively (both comparisons p < 0.01) Well tolerated Use of iron sucrose for general women’s health Krayenbuehl et al (2011) [ 94 ] Hb ≥ 12.0 g/dL SF ≤ 50 ng/mL IS: 43 Placebo: 47 200 mg q.d., 4 days Trend for better improvement of fatigue score with IS versus placebo 21% drug-related AEs with IS (nausea, chills, headache, dizziness, chest pain, dysesthesia, dysgeusia), 7% AEs with placebo (nausea, headache, dizziness, diarrhea) Lee et al (2019) [ 96 ] Menorrhagia Hb < 10 g/dL SF < 30 ng/mL IS: 49 FCM: 52 IS: 200 mg q.d. (≤ 600 mg/week) FCM: < 50 kg, 500 mg/week; ≥ 50 kg, 1000 mg/week FCM was as effective as IS in achieving Hb ≥ 10 g/dL within 2 weeks after first administration (78.8% vs. 72.3%).…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…If she is unresponsive or intolerant, I would initiate IV iron with the third-generation ferric carboxymaltose (INJECTAFER), which is simple and well tolerated, in 2 doses 7 days apart. 17,19 Carboxymaltose (INJECTAFER) is also more effective in fewer doses and results in a greater and more rapid increase in hemoglobin in women with iron-deficiency anemia in pregnancy compared with iron sucrose, the previous standard of care in pregnancy. 20 In addition to the burden of iron deficiency, quality of life in WBD is poor and associated with a delay in diagnosis and poor access to treatment.…”
Section: The Hematologist's Viewmentioning
confidence: 99%
“…Delay in diagnosis, difficulty accessing treatment 21 VWF levels masked by hormones, pregnancy, comorbidities 7,8 VWF assay high variability 9,10 Iron-deficiency anemia 15 Poor cognitive, social functioning, quality-of-life [21][22][23] Malposition, expulsion of intrauterine device 26 II. Current approach to management Iron supplementation [17][18][19] Tranexamic acid 24 Levonorgestrel intrauterine device 26 Combined oral contraceptive 24 VWF concentrate 24 effect by releasing hormone into the endometrial cavity but is limited by weight gain and depression in 20% of patients, and it may be expelled as a result of large clot burden. 26 VWF concentrate replaces defective or deficient VWF protein but is limited by invasiveness and cost.…”
Section: Clinical Burden Of Hmbmentioning
confidence: 99%